Strengthening MSME Resilience After Crisis: The Role of Business Culture, Social Capital, and Digital Literacy (A Study on MSMEs in Makassar) - Sri Adrianti Muin; Syamsuddin B; Virza Hadrianti; Rachmat Sugeng (Journal of Economics and Management, 2026)
This study aims to analyze the influence of local business culture, social capital, and digital literacy on the post-crisis resilience of MSMEs in South Sulawesi. Resilience is defined as the ability of business actors to survive, adapt, and recover after experiencing a crisis. This study employs a quantitative approach based on the SmartPLS method. The sample consists of MSME actors who are still actively running their businesses and have experienced an economic crisis or pandemic, totaling 200. Business culture has been shown to significantly influence MSME resilience, both directly and through the mediating role of digital literacy. Social capital does not directly affect resilience, but it does have a significant relationship with digital literacy. Digital literacy serves as a strategic link between cultural values and social networks in strengthening business resilience. This study offers a novel contribution by integrating three approaches—business culture, social capital, and digital literacy—into a single structural model. This study also enriches the literature by highlighting the local context, grounded in Bugis-Makassar ethnic cultural values, in shaping MSME resilience after the crisis.